Review on Experimental Treatment Strategies Against Trypanosoma cruzi - Mazzeti AL; Capelari-Oliveira P; Bahia MT; Mosqueira VCF (Dove Medical Press, 2021)
Ana Lia Mazzeti,1– 3 Patricia Capelari-Oliveira,1 Maria Terezinha Bahia,3 Vanessa Carla Furtado Mosqueira1 1Laboratório de Desenvolvimento Galênico e Nanotecnologia, Escola de Farmácia, Universidade Federal de Ouro Preto, Ouro Preto, Minas Gerais, 35400-000, Brazil; 2Laboratório de Biologia Celular, Instituto Oswaldo Cruz, Fundação Oswaldo Cruz, Rio de Janeiro, Rio de Janeiro, 21040-360, Brazil; 3Laboratório de Doenças Parasitárias, Escola de Medicina & Núcleo de Pesquisas em Ciências Biológicas, Universidade Federal de Ouro Preto, Ouro Preto, Minas Gerais, 35400-000, BrazilCorrespondence: Vanessa Carla Furtado MosqueiraLaboratório de Desenvolvimento Galênico e Nanotecnologia, Escola de Farmácia, Universidade Federal de Ouro Preto, Morro do Cruzeiro, Ouro Preto, MG, 35400-000, BrazilTel +55 31 3559-1032Email mosqueira@ufop.edu.brAbstract: Chagas disease is a neglected tropical disease caused by the protozoan Trypanosoma cruzi. Currently, only nitroheterocyclic nifurtimox (NFX) and benznidazole (BNZ) are available for the treatment of Chagas disease, with limitations such as variable efficacy, long treatment regimens and toxicity. Different strategies have been used to discover new active molecules for the treatment of Chagas disease. Target-based and phenotypic screening led to thousands of compounds with anti-T. cruzi activity, notably the nitroheterocyclic compounds, fexinidazole and its metabolites. In addition, drug repurposing, drug combinations, re-dosing regimens and the development of new formulations have been evaluated. The CYP51 antifungal azoles, as posaconazole, ravuconazole and its prodrug fosravuconazole presented promising results in experimental Chagas disease. Drug combinations of nitroheterocyclic and azoles were able to induce cure in murine infection. New treatment schemes using BNZ showed efficacy in the experimental chronic stage, including against dormant forms of T. cruzi. And finally, sesquiterpene lactone formulated in nanocarriers displayed outstanding efficacy against different strains of T. cruzi, susceptible or resistant to BNZ, the reference drug. These pre-clinical results are encouraging and provide interesting evidence to improve the treatment of patients with Chagas disease.Keywords: Trypanosoma cruzi, drug discovery, new chemical entities, repurposing, drug combination, nanomedicine